2013
DOI: 10.1530/jme-13-0059
|View full text |Cite
|
Sign up to set email alerts
|

Globular adiponectin induces LKB1/AMPK-dependent glucose uptake via actin cytoskeleton remodeling

Abstract: Previous studies have shown that many metabolic actions of adiponectin are mediated via the activation of AMP kinase and that adiponectin stimulates GLUT4 translocation and glucose uptake in the muscle. In this study, we demonstrate that adiponectin stimulates actin cytoskeleton remodeling, with increased phosphorylation of cofilin, and that blocking of cytoskeletal remodeling with cytochalasin D prevents adiponectin-stimulated AMPK phosphorylation in L6 myoblasts. LKB1 is an upstream kinase of AMPK, and we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Recent studies have also shown that the LKB1/AMPK pathway is implicated in adiponectin-induced various biologic responses. For example, adiponectin-induced glucose uptake and suppression of breast cancer cells migration are mediated via LKB1/AMPK-dependent manner (Vu et al, 2013). Although it is well known that LKB1 is implicated in adiponectin-induced biologic responses, the role of LKB1 signaling in antioxidative effect induced by adiponectin has not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also shown that the LKB1/AMPK pathway is implicated in adiponectin-induced various biologic responses. For example, adiponectin-induced glucose uptake and suppression of breast cancer cells migration are mediated via LKB1/AMPK-dependent manner (Vu et al, 2013). Although it is well known that LKB1 is implicated in adiponectin-induced biologic responses, the role of LKB1 signaling in antioxidative effect induced by adiponectin has not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, LKB1 deficiency leads to inactivation of AMPK, and LKB1-induced tumor suppression and modulation of cellular energy homeostasis are mediated through activation of AMPK (Shaw et al, 2004;Alessi et al, 2006). Furthermore, LKB1/AMPK axis is used for adiponectininduced various biologic responses (Miller et al, 2011;Vu et al, 2013). However, the effect of adiponectin on LKB1 signaling and its role in the modulation of ROS production in macrophages have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Adiponectin directly regulates glucose metabolism and insulin sensitivity. Adiponectin, via activation of AMPK and adiponectin, stimulates GLUT4 translocation and glucose uptake [124]. Adiponectin receptors activate AMPK, PPAR- α , and p38 MAPK to increase insulin sensitivity [58, 125].…”
Section: Adiponectin Aging and Diabetesmentioning
confidence: 99%
“…Glucose uptake assays were performed in C2C12 and L6 myotubes using 2-deoxy- [ 3 H]-glucose as tracer as described in our previous study (20). For ex vivo glucose uptake assay, mice fasted for 4 h were anesthetized.…”
Section: Analysis Of Glucose Uptake and Glut4 Translocation In Musclementioning
confidence: 99%
“…Isolated extensor digitorum longus (EDL) or soleus muscles were stimulated without or with insulin 60 mU/mL followed by measurement of 2-deoxy-[ 3 H]-glucose uptake (21). For determination of GLUT4 translocation, an antibodycoupled densitometric assay was used to measure the content of surface Myc-GLUT4 in L6 myotubes stably expressing Myc-tagged GLUT4 as described in previous studies (20,22).…”
Section: Analysis Of Glucose Uptake and Glut4 Translocation In Musclementioning
confidence: 99%